Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13054-018-2095-9
|View full text |Cite
|
Sign up to set email alerts
|

Early application of continuous high-volume haemofiltration can reduce sepsis and improve the prognosis of patients with severe burns

Abstract: BackgroundIn the early stage of severe burn, patients often exhibit a high level of inflammatory mediators in blood and are likely to develop sepsis. High-volume haemofiltration (HVHF) can eliminate these inflammatory mediators. We hypothesised that early application of HVHF may be beneficial in reducing sepsis and improving the prognosis of patients with severe burns.MethodsAdults patients with burns ≥ 50% total burn surface area (TBSA) and in whom the sum of deep partial and full-thickness burn areas was ≥ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 44 publications
(54 reference statements)
0
56
0
3
Order By: Relevance
“…Two RCT studies did not nd that CRRT had a positive effect on the mortality of burn patients (51, 52). You 2018 (10) found that early HVHF treatment may reduce 90-day mortality of patients with severe burns (≥ 80% TBSA) (P = 0.049). A meta-analysis of these three RCT studies also did not show that CRRT could reduce the risk of death in burn patients with AKI compared with the standard care (non-RRT) (RR = 0.64, 95%CI 0.40-1.03, P = 0.06; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two RCT studies did not nd that CRRT had a positive effect on the mortality of burn patients (51, 52). You 2018 (10) found that early HVHF treatment may reduce 90-day mortality of patients with severe burns (≥ 80% TBSA) (P = 0.049). A meta-analysis of these three RCT studies also did not show that CRRT could reduce the risk of death in burn patients with AKI compared with the standard care (non-RRT) (RR = 0.64, 95%CI 0.40-1.03, P = 0.06; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three RCT studies compared the effects of standard care (non-RRT) and CRRT on patients' prognosis (10,51,52). Two RCT studies did not nd that CRRT had a positive effect on the mortality of burn patients (51, 52).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute kidney injury associated with sepsis has a distinct pathophysiology [7], and septic patients with AKI may have a different response to renal replacement therapy (RRT) than those patients without sepsis [8,9]. RRT is known to improve the survival rate of patients with AKI in ICU, because it rectifies metabolic acidosis by removing lactate, regulating unmeasured anions and adjusting levels of phosphate and chloride [10,11]. It is widely consentient that if there are lifethreatening complications for septic patients with AKI, such as hyperkalemia, metabolic acidosis and acute pulmonary edema, RRT should be started immediately [5,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%